GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (IESE Conference - Challenges of social and economic research in times of crisis, 2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Laws and Regulations Related to Foreign Direct Investment in Mozambique - JLA Advogados (Agency for Promotion of Investment and Exports (APIEX), 2017)
After becoming an independent State, Mozambique was plagued by a long and severe civil war, which ultimately resulted in an economic collapse led by the lack of investment, nationalization of privately owned industries, as well as widespread food shortage. The 1992 peace agreement marked the transition from civil war to peace, culminating in the country’s first democratic elections of 1994 and the emergence of the Front for the Liberation of Mozambique (Frelimo) as the dominant political force in the country; a fact that still holds true today. In 1993 the Mozambican Government approved the Investment Act to foster and promote both national and foreign investmentsin the country, granting various benefits and incentives, which include: tax and custom duties exemptions, free remittance of funds, and the possibility of hiring more foreign workers than those permitted by law. These incentives vary according to the economic and industrial activity pursued and the region of implementation of the project. Mozambique’s rapid economic expansion over the past decades has had only a moderate impact on poverty reduction, and the geographical distribution of poverty remains largely unchanged. Despite the recent discoveries of natural resources in the oil & gas sectors, Mozambique is undergoing serious economic and political crisis and needs to improve its social indicators. The country ranked 178th out of 187 countries in the most recent Human Development Index (HDI). The adult literacy rate is 56% (fifty six percent), and average life expectancy at birth is just 50,3 (fifty point three) years. In January 2015, after the 5th (fifth) peaceful election process, Mozambique’s fourth president came into office Mr. Filipe Nyusi. His party also secured a strong majority in the parliament, with 144 seats out of 250 in total.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês

Managing for Sustainable Development Impact - Kusters, Cecile; Batjes, Karen; Wigboldus, Seerp; Brouwers, Jan; Baguma, Sylvester Dickson (Practical Action Publishing Ltd, 2017)
This guide is about managing development initiatives and organizations towards sustainable development impact. It builds on the work of Guijt and Woodhill in the 2002 IFAD publication Managing for Impact in Rural Development: A Guide for Project M&E. Since then, the managing for sustainable development impact (m4sdi) approach has evolved with insights and feedback from CDI colleagues, clients, partners, and over 800 people who have been trained in its use. In addition, the authors have drawn on the work of many others. m4sdi is an integrated, results-oriented management approach, which can be used across a range of sectors and domains in a variety of contexts, and aims to contribute towards the Sustainable Development Goals (SDGs). It seeks to integrate ideas and practices from a range of approaches and methodologies for planning, monitoring and evaluation, using appropriate methods or tools that engage people in a process of learning and adaptation. It is specifically aimed at strengthening the readiness of leaders, decision-makers and development practitioners to effectively manage their initiatives/organizations in complex settings. m4sdi belongs to a special niche of management approaches, providing relevant perspectives on what makes for effective management for those directly involved in managing initiatives/organizations and wider groups of stakeholders. Many of the people trained in m4sdi have become believers and practitioners of the approach because it addresses several of the most serious concerns in development, such as the difficulty in reaching primary stakeholders, designing effective strategies and related monitoring and evaluation (m&e), focusing on capacity development and change management, and achieving sustainable development impact. The strength of m4sdi lies in its people-centred approach and how it seeks to integrate management processes within a complex environment. The evolvement of the approach needs to be documented to share lessons learned and support capacity development. And so the principles and practices covered in this guide relate to a variety of development initiatives/organizations in the fields of agriculture, food security, local economic development, value chains, enterprise development, and ecosystem governance. Much of the discussion takes place within the often complex context of development. As such, the guide aims to find a good balance between comprehensiveness and the principle of ‘less is more’.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (NUPI political economy reports, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental